Evaluation of the quality of clinical guidelines for prophylaxis of venous thromboembolism in urological surgeries by the AGREE II review instrument. Issue 2 (16th February 2023) - Shakiba, Behnam; Kabir, Ali; Irani, Shirin; Torabi, Nasim; Nourmohamad, Vahid; Farid, Mohaddese
Abstract: Background and Aims: Venous thromboembolism (VTE) is the most common cause of death during the first 30 days after surgery. There is not any study which critically evaluated clinical guidelines related to VTE prophylaxis in urological surgeries. Therefore, in this study, we decided to evaluate related clinical guidelines using the AGREE II instrument to take a positive step towards improving the care of these patients. Methods: The latest version of all available clinical guidelines related to the topic of VTE prophylaxis in urological surgeries until 2021 was searched. Four appraisers, including one urologist, one cardiologist, one epidemiologist, and one MD who had prior knowledge of working with the AGREE II tool and international articles in this field appraised selected clinical guidelines. Using the AGREE II review tool, clinical guidelines were critically evaluated. Then, the score of six domains of AGREE II for each guideline was calculated and compared with each other, and the relationship between the domains was measured by Kendall's correlation test. To determine the reliability of the test, interclass correlation coefficients were calculated for all indicators. Results: Items were rated on a 7‐point scale from 1 (strongly disagree) to 7 (strongly agree). NICE, CHEST, and EAU guidelines obtained the highest scores from the Overall Assessment criteria by scoring 6, 5.75, and 5.25, respectively. There was only a correlation between the score of Overall Assessment criterion with "Applicability" domain, with Kendall's correlation coefficient of 0.867 and p = 0.015. The domains of "Clarity and presentation" and "Scope and purpose" obtained the highest standardized scores by getting 84.49% and 75.69%, respectively, and "Applicability" with 30.04% obtained the lowest standardized score. Conclusion: In this study, NICE, CHEST, and EAU guidelines are suggested as clinical guidelines by obtaining the highest scores from Overall Assessment criterion.